2021
DOI: 10.1039/d1ra00012h
|View full text |Cite
|
Sign up to set email alerts
|

Phosphotungstic acid impregnated niobium coated superparamagnetic iron oxide nanoparticles as recyclable catalyst for selective isomerization of terpenes

Abstract: Conversion efficiency as high as 80–100% and 50% selectivity for camphene and limonene was achieved with low production of polymeric byproducts (18–28%), using a new magnetically recyclable catalyst – SPION-Nb30@HPW.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…It is worth to notice that the conversion observed with the capsule was comparable to that what was frequently observed with typical heterogeneous Lewis or Brønsted catalysts under harsher experimental conditions with T higher than 100 °C in the gas phase [ 61 ]. More importantly, the product distribution observed is rather unusual if compared to many other heterogeneous catalytic systems known in the literature for leading to higher selectivity for camphene [ 62 66 ], and less likely to comparable amounts of camphene and limonene [ 67 68 ]. The preferential formation of limonene, which compared to camphene is a much more valuable product, has been less frequently observed, for instance in the case of heteropolyacids on SBA-15 [ 69 ].…”
Section: Resultsmentioning
confidence: 86%
“…It is worth to notice that the conversion observed with the capsule was comparable to that what was frequently observed with typical heterogeneous Lewis or Brønsted catalysts under harsher experimental conditions with T higher than 100 °C in the gas phase [ 61 ]. More importantly, the product distribution observed is rather unusual if compared to many other heterogeneous catalytic systems known in the literature for leading to higher selectivity for camphene [ 62 66 ], and less likely to comparable amounts of camphene and limonene [ 67 68 ]. The preferential formation of limonene, which compared to camphene is a much more valuable product, has been less frequently observed, for instance in the case of heteropolyacids on SBA-15 [ 69 ].…”
Section: Resultsmentioning
confidence: 86%
“…Other uses are in [3+2+2] cycloaddition [19] and ring-opening polymerization of epoxidized soybean oil. [20] In the context of our ongoing efforts to transform biomass turpentine into valuable chemicals [21][22][23], HSbF 6 was used as catalyst for the direct esterification of turpentine oil with acetic acid as reactant and solvent. Herein, it is shown that this superacid can greatly improve the reaction rate, due to its high acidity, providing excellent conversion and selectivity of the product of interest, i.e., the fraction of terpenyl acetate formed in relation to the total products.…”
Section: Introductionmentioning
confidence: 99%